Analisis Reaksi Pasar Modal Terhadap Pemilu Presiden Indonesia Tahun 2024 - Pratama, Muhammad Raihan; Handarini, Dwi; Zairin, Gentiga Muhammad (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
This study was conducted to determine the reaction of the Indonesian capital market to the 2024 Indonesian Presidential election event.The sample in this study was taken by purposive sampling method with the results of 921 companies listed on the Indonesia Stock Exchange (IDX). This study uses secondary data obtained from the official IDX website. Hypothesis testing in this study using the Wilcoxon Test with the results found significant differences in abnormal returns before and after the announcement of election results by the KPU and the reading of the Constitutional Court's decision. There was no significant difference in trading volume activity before and after the announcement of the election results but a significant difference was found before and after the reading of the Constitutional Court's decision.